A critical examination of rural out-migration studies in Ethiopia: considering impacts on agriculture in the sending communities - Dessalegn, Mengistu; Debevec, L.; Nicol, Alan; Ludi, Eva (MDPI, 2023)
Labor migration is a complex phenomenon, yet while much attention has been paid to understanding the drivers of migration, there is a huge knowledge and policy gap regarding the effects of migration on people and communities left behind. We sought to explore the impacts of rural outmigration on migrant-sending communities in Ethiopia. This remains an understudied topic when it comes to research on migration in Ethiopia. Our investigation is based on a critical review of the migration literature pertaining to Ethiopia and, more broadly. We pursued a holistic analysis of the multidimensional aspects of migration. There are indications that rural outmigration impacts involve issues related to remittances, household food security, agricultural labor use, farmland management, and rural infrastructure development. Our analysis revealed that there had been few systematic studies and limited analyses regarding the impacts of outmigration on agriculture and the livelihoods of rural people and households left behind. Instead, Ethiopia’s migration literature largely deals with migration’s causes, including environmental factors, climate variability, agricultural pressures, livelihood stresses, and changing aspirations.